The Principle of Legal Certainty of Registration Motion Marks Based on Law Number 20 of 2016 Concerning Trademarks and Geographical Indications - Gema Permana Rahman; Suherman Suherman; Diani Sadiawati (Green Social: International Journal of Law and Civil Affairs, 2025)
In the development of information and technology, there are motion marks circulating in Indonesia in the trade of goods or services. In fact, the moving brand has not received legal protection because moving brands are not regulated as one of the signs regulated in Law Number 20 Year 2016 on Trademarks and Geographical Indications (Trademark Act) so that there is a legal vacuum and a motion marks can not be applied for registration which results in the absence of legal certainty for the community, but other Southeast Asian countries such as Singapore have protected motion marks. It is important to be considered by Indonesia, given the existence of free trade in the Southeast Asian region, namely the ASEAN Free Trade Area (AFTA). This research uses normative juridical research method that analyses the legislation with literature study using comparative and conceptual approaches and analysed with descriptive analytical legal materials. The results of this study found that the regulation of the registration of motion marks in Indonesia is not regulated in the Trademark Act and the trademark registration application does not accommodate the registration of motion marks so that the registration of moving trademarks can not be filed in Indonesia and motion marks also do not get legal protection in Indonesia which results in legal uncertainty. If the motion marks in Indonesia get a legal protection and can be applied for registration, then the Trademark Act should be made changes related to the concept of the definition of trademark, the scope of the protected trademark, and trademark labels in the application for registration of trademarks so that the public get legal certainty related to the registration of motion marks.